PERILAKU CYBERSEX DI MEDIA SOSIAL FACEBOOK (Analisis Wacana pada Akun Grup “Cerita Bikin Basah”) - Makaria Asriana Hadia; Hotlif A. Nope; Susana C. L. Pellu (Jurnal Pluralis, 2023)
Social Media is online or online media that is used as a means of social interaction on the internet. The positive impact of using social media is that people can easily carry out activities on social media, such as communicating or interacting to providing information or content in the form of photo and video writing, along with increasing use of social media there are also negative impacts, one of which is cybersex. Cybersex is anything posted on social media, be it in the form of writing, pictures, videos, or statuses that mix sexually. The formulation of the problem in this research is what is the meaning of the language of status updates for group members "makes stories wet" on the Facebook application. The purpose of this study is to analyze the meaning of language from the status uploads of group members "makes us wet stories" on the Facebook application. The theory used in this study is the discourse analysis theory of Teun Van Dijk. The method in this research is qualitative with explanatory research. The technique used in this study was purposive sampling and the number of informants in this study was 32 people. The criteria for the selected informants were: 19 members of the "make it wet story" group who actively shared status and 13 members of the make it wet story group commented on status. The results of this study indicate that the status and comments of the members of the "story makes wet" group, the use of language meaning related to Van Dijk's discourse analysis, especially from the thematic, schematic, syntactic and semantic points of view describe the existence of sexual desire or lust which leads to sexual deviance by cybersex offenders, based on Van Dijk's discourse analysis on the meaning of language related to discussion in the group account "stories make you wet" has sections related to cybersex behavior such as sex chat, sex phone, sex video calls and tells in the form of a chronological status having sex. In addition, the discussion in the group "the story makes you wet" the group members use words and sentences that are irregular and are inviting or lead to deviant things, namely cybersex. The use of these words shows that group members are both cybersex offenders. The advice given is: For people who use social media, they should use the Facebook application according to its function, people should understand ethics in using social media such as being wise in using Facebook. Entities in Indonesia that monitor internet usage must be more careful so that sites that allow access to cybersex are quickly blocked. Family institutions and educational institutions are required to provide sex education from an early age in accordance with the level of demands for sex education, and through character building so that children know what is good and what is not good in physical control when growing up.